Intravoxel incoherent motion imaging has the possibility to detect liver abnormalities in young Fontan patients with good hemodynamics. (28th June 2019) - Shiraga, Kazuhiro; Ono, Kojiro; Inuzuka, Ryo; Asakai, Hiroko; Ookubo, Takumi; Shirayama, Akira; Higashi, Kouji; Nakajima, Hiromichi
Abstract: Introduction: Liver fibrosis and cirrhosis are one of the critical complications in Fontan patients. However, there are no well-established non-invasive and quantitative techniques for evaluating liver abnormalities in Fontan patients. Intravoxel incoherent motion diffusion-weighted imaging with MRI is a non-invasive and quantitative method to evaluate capillary network perfusion and molecular diffusion. The objective of this study is to assess the feasibility of intravoxel incoherent motion imaging in evaluating liver abnormalities in Fontan children. Materials and Methods: Five consecutive Fontan patients and four age-matched healthy volunteers were included. Fontan patients were 12.8 ± 1.5 years old at the time of MRI scan. Intravoxel incoherent motion imaging parameters (D, D*, and f values) within the right hepatic lobe were compared. Laboratory test, ultrasonography, and cardiac MRI were also conducted in the Fontan patients. Results of cardiac catheterization conducted within one year of the intravoxel incoherent motion imaging were also examined. Results: In Fontan patients, laboratory test and liver ultrasonography showed almost normal liver condition. Cardiac catheter and MRI showed good Fontan circulation. Cardiac index was 2.61 ± 0.23 L/min/m 2 . Intravoxel incoherent motion imaging parameters D, D*, and f values were lower in Fontan patients compared with controls (D: 1.1 ± 0.0 versus 1.3 ± 0.2 × 10 −3 mm 2 /second (p = 0.04), D*: 30.8 ± 24.8 versus 113.2 ± 25.6 × 10 −3 mm 2 /second (p < 0.01), and f: 13.2 ± 3.1 versus 22.4 ± 2.4% (p < 0.01), respectively). Conclusions: Intravoxel incoherent motion imaging is feasible for evaluating liver abnormalities in children with Fontan circulation.